Answer:
![(-8 +2√(3) )/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/no6wu0zmokjticmuyy3v2vdj6x5rqu9y2m.png)
Explanation:
When working with surds we need to take note of the roots present there.
To expand this equation we can do it the following way noting that √3 X √3 = 3
Expanding (1-√3)(⅓+√3)
1 X 1/3 = 1/3
1 X √3 = √3
-√3 X 1/3 =-√3/3
√3 X √3 = 3
hence, expanding the equation, we have
1/3 + √3 -√3/3 + 3
We can simply group the like terms and add them up.
[1/3 +3] +[√3-√3/3]
10/3 +
![(2√(3) )/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/o7a0o7q9m4a7w38lot0c477gf7sdgt71t1.png)
=
![(-8 +2√(3) )/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/no6wu0zmokjticmuyy3v2vdj6x5rqu9y2m.png)